2017
DOI: 10.1515/pac-2017-0610
|View full text |Cite
|
Sign up to set email alerts
|

Calibration, standardization, and quantitative analysis of multidimensional fluorescence (MDF) measurements on complex mixtures (IUPAC Technical Report)

Abstract: This IUPAC Technical Report describes and compares the currently applied methods for the calibration and standardization of multi-dimensional fluorescence (MDF) spectroscopy data as well as recommendations on the correct use of chemometric methods for MDF data analysis. The paper starts with a brief description of the measurement principles for the most important MDF techniques and a short introduction to the most important applications. Recommendations are provided for instrument calibration, sample preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…IFE is usually considered a problem because it causes a nonlinear dependence between intensity and concentration. However, it is a valuable source of information about protein‐based samples because of the high sensitivity to changes in sample composition (Panigrahi & Mishra, 2019 ; Ryder et al, 2017 ) and can be incorporated into variance assays once identified and taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…IFE is usually considered a problem because it causes a nonlinear dependence between intensity and concentration. However, it is a valuable source of information about protein‐based samples because of the high sensitivity to changes in sample composition (Panigrahi & Mishra, 2019 ; Ryder et al, 2017 ) and can be incorporated into variance assays once identified and taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…This effectively prevents the use of absorbance spectroscopy as a quantitative method for in‐process protein analysis. This high absorbance also causes very strong IFE, which has a significant impact on UV fluorescence (Ryder et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Inner-filtering is an artifact caused by the absorption of excitation and emission light and is greatest at the shortest EEM wavelengths . Inner-filtering effects could either be (1) intentionally removed by sample dilution or algorithmic correction methods or (2) utilized as the intrinsic characteristic of the sample …”
Section: Resultsmentioning
confidence: 99%